CHINA POLICY ON GIVING FOREIGN AID IN THE FORM OF GRANTS TO INDONESIA IN 2016 - Aditya Pangestu; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study aims to analyze the China foreign policy which giving a grant of 30 million RMB yuan to Indonesia. in 9 May 2016 China agreed on economic and technical assistance with Indonesia for infrastructure development in Indonesia. at the same time, in 2015 China has started the implementation of the Belt and Road initiative (BRI) project and Indonesia is included in one part of the project. Then the author tries to reveal the motive for China foreign aid in giving these grants.This study uses the concept of foreign policy and the motive of foreign assistance, using the theory of foreign aid by Degnbol-Martinussen and Engberg-Pedersen and the methodology used in this study is a qualitative explanative method. This method is carried out by collecting data by researching, compiling, interpreting and explaining the data or phenomena that occur, then continued by trying to reveal and analyze the phenomenon or incident related to the problem under study. The research results show that China's foreign policy has a motive towards Indonesia, which every year there is also an increase in loans and investment in the development sector of China projects in Indonesia. To accelerate the work on projects whose funds come from China loans and investments, China in 2016 giving foreign assistance in the form of a 30 million RMB yuan grant to Indonesia for economic and technical assistance. because Indonesia is included in the Belt and Road Initiative (BRI) project, the motive for the grant is intended for infrastructure development related to BRI. and in giving these grants China made its image better and then it would make Indonesia dependent on its infrastructure development. Keywords: Foreign Aid, Belt and Road Initiative (BRI), China Motive, Infrastructure Development